Plasma metabolites of receiving heifers and the relationship between bovine respiratory disease, weight gain, and carcass characteristics - Sean P. Montgomery; J.J. Sindt; M.A. Greenquist; W.F. Miller; J.N. Pike; E.J. Good; E.R. Loe; M.J. Sulpizio; T.J. Kessen; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2004)
Six hundred sixty-five crossbred beef heifers initially weighing 495 lb were used to evaluate rectal temperature and plasma glucose, lactate, and urea nitrogen at initial processing as indicators of health status of newly arrived receiving cattle. We also evaluated the relationship between bovine respiratory disease (BRD), weight gain, and carcass characteristics. An increased number of treatments for BRD was associated with lower (linear, P<0.01) plasma glucose and lactate concentrations at initial processing. Elevated rectal temperatures at initial processing were associated with a greater number of treatments for BRD (linear, P<0.03). Initial body weight, final body weight, and average daily gain during the receiving period were progressively less (linear, P<0.01) as the number of treatments for BRD increased, whereas grazing-period gain was progressively greater with more frequent treatment for BRD during the receiving period (linear, P<0.01). Finishing-period gain, final body weight, hot carcass weight, fat thickness, and marbling score were linearly decreased (P<0.05) with increased treatmentfor BRD during the receiving period. These data suggest that initial plasma glucose and lactate concentrations might be associated with the health of newly arrived receiving cattle and that increased incidence of BRD in cattle is associated with lower weight gain and carcass quality.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Plasma metabolites; Bovine respiratory disease; Weight gain; Carcass characteristics